How to Blackout-Proof A City. - Goldstein, H.
Mumbai has enjoyed plentiful and reliable power for a century. But this year Mumbai's economic miracle threatens to overwhelm the power grid. This paper presents on how to get through the tropical summer without significant load shedding or blackouts. The power companies in Mumbai gave a public-awareness campaign for citizens to conserve 20 percent of energy usage
Keywords: Mumbai; Blackout-proof.; Energy conservation; Load shedding; Power companies; Power consumption; Power grid